A SERVICE PERSPECTIVE OF LUXURY TOURISM - Ni Luh Eka Armoni; Ni Made Ernawati; I Wayan Jendra (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
This paper reporting the service aspect of luxurious tourism, is a part of a broader study identifying elements constitute luxurious travels. It is a qualitative study involved 48 respondents who are members of 7 different Facebook travel groups. Data collection was conducted by posting a discussion topic on luxury travels to the Facebook groups. It is identified that service of luxurious tourism products is premium and personalized, wherein VIP handling is not a special service, rather a basic standard that needs to be met for elite customers. It is the ability to satisfy customers beyond expectation, exclusive supreme products only few people can afford, which is not easy to be provided. Nevertheless, above and beyond the design and the delivery of the exclusive high quality services and after performing the very best effort; luxurious service sometimes means serving customers with heart and sincerity reaching the human side of people; meeting the needs of high class customers intuitively, when facing and anticipating matters beyond human control. It is expected that the analysis could enrich the discourse on luxurious tourism products, assist in resolving the puzzle of a perfect service, perfecting the imperfect.